Transcriptional profiles reveal a stepwise developmental program of memory CD8+ T cell differentiation. Issue 7 (11th February 2015) - Roychoudhuri, Rahul; Lefebvre, Francois; Honda, Mitsuo; Pan, Li; Ji, Yun; Klebanoff, Christopher A.; Nichols, Carmen N.; Fourati, Slim; Hegazy, Ahmed N.; Goulet, Jean-Philippe; Gattinoni, Luca; Nabel, Gary J.; et al.
Highlights We perform whole transcriptome analysis of distinct CD8+ T-cell memory populations arising endogenously following immunization with clinical and pre-clinical vaccines regimens. We find that transcriptional proximity relationships between endogenous TN, TCM, TEM and TEFF place memory cells at an intermediate state of differentiation between TN and TEFF. We compare transcriptional differences between TN, TCM, TEM and TEFF cells with known changes when CD8+ T cells undergo repeated antigen stimulation. We find that at a single time-point following vaccination, cells can be found with the transcriptional imprint of distinct exposures to antigen. Our analysis favors the progressive differentiation model whereby cumulative antigen stimulation drives differentiation specifically from TN > TCM > TEM > TEFF.